Continuous Viscosity Solutions for Nonlocal Dirichlet Problems with Coercive Gradient Terms - Topp-Paredes, E (Springer New York LLC, 2017)
In this paper we study existence of solutions of nonlocal Dirichlet problems that include a coercive gradient term, whose scaling strictly dominates the one of the integro-differential operator. For such problems the stronger effect of the gradient term may give rise to solutions not attaining the boundary data or discontinuous solutions on the boundary. Our main result states that under suitable conditions over the right-hand side and boundary data, there is a (unique) Hölder continuous viscosity solution attaining the boundary data in the classical sense. This result is accomplished by the construction of suitable barriers which, as a byproduct, lead to regularity results up to the boundary for the solution. © 2016, Springer-Verlag Berlin Heidelberg.